The Networks of Consecration: The Journey of Magda Szabó and László Krasznahorkai’s International Reputation One - Varga, Zsuzsanna (Porównania, 2020)
This chapter focuses on the international reputation of the work of two Hungarian novelists the late twentieth and early twenty-first centuries: the reception of the novels of Magda Szabó and László Kraszahorkai in German, French and English literary cultures. Though different in novelistic approach, genre and aesthetics, they belong to a small group of Hungarian writers whose work found resonance with the international readership. The chapter argues that their international circulation, reception and popularity are much entwined with very tangible processes of mediation through networks of translators and other cultural agents active in the international economy of letters.